PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH DAN KOMUNIKASI MATEMATIS MAHASISWA PGSD MELALUI PENDEKATAN SAINTIFIK - Sukriadi Hasibuan; Novri Yaldi (Institut Pendidikan Tapanuli Selatan, 2019)
The purpose of this study is to see how far the improvement of mathematical problem solving and mathematical communication abilities of PGSD students at the South Tapanuli Institute of Education taught by using a scientific approach, 36 students use class action research consisting of cycle I and cycle II with planning stages , implementation, observation and reflection. Data processing used is qualitative and quantitative, for data collection using observations and tests to see the level of research success. The results of this study can be concluded that (1) there is an increase in students' mathematical problem solving abilities by using a scientific approach seen from the percentage of completeness of the first cycle 52.78%, and the second cycle is 88.89%. (2) there is an increase in students' mathematical communication skills using a scientific approach with the percentage level of completeness in the first cycle is 55.56%, and the second cycle is 83.33%. the conclusion of this research is that using a scientific approach can improve learning outcomes of mathematical problem solving and communication of PGSD students at the South Tapanuli Institute of Education.